Suplicatorio y política: Praxis parlamentaria y claves del debate doctrinal sobre el control jurisdiccional de la potestad denegatoria de los suplicatorios - Tshitshi Ndouba, Kayamba (Revista de Derecho Político, 2018)
Resumen: El presente artículo aborda algunos problemas entre política y derecho que genera la decisión parlamentaria en la concesión o denegación de los suplicatorios. Por ello, analiza la praxis de los suplicatorios tramitados por el Congreso de los diputados y el Senado hasta la fecha, poniendo énfasis en la doctrina emanada de las decisiones adoptadas por las comisiones parlamentarias competentes. Para profundizar en la interacción entre suplicatorio, política y derecho, el artículo indaga en los pasos cualitativos y saltos prominentes de la evolución de la jurisprudencia constitucional sobre los límites de la facultad de las Cámaras para conceder o denegar el suplicatorio. Recaba y sistematiza el tratamiento académico de los puntos clave del debate emanado de estos sucesivos pronunciamientos del TC: las implicaciones de esta jurisprudencia en relación a los postulados constitucionales de independencia y ordenación de los poderes del Estado, las definiciones de criterios jurídicos que han de inspirar y guiar a las Cámaras para autorizar o denegar el suplicatorio, la concreción del modelo y la estructura de ponderación aplicables en los casos de colisión de dos derechos fundamentales (en este caso, los arts. 23 y 24 de la Constitución española [CE]). Summary: I. Praxis of the Parliamentary Procedure for the Waiver of Immunity. II. The Request to Waive the Parliamentary Immunity Before the Constitutional Court. Issues With Undeniable Constitutional Significance. III. The Constitutional Court and the Judicial Review of the Requests to Waive the Parliamentary Immunity. 1. Interna corporis acta and fundamental rights. 2. «Trial of opportunity» and the formal «requirement of a statement of reasons». 3. The degree of providing an adequate statement of reasons in the denial court’s decision. 4. The question of weighing up different values against one another: fundamental rights and the Parliament members’ prerogatives. IV. The Doctrinal Debate on the Constitutional Court’s Jurisprudence. 1. Emptying the parliamentarian immunity and the issue of «checks and balance» of State’s constitutional powers.2. Opposing the parliamentary immunity and the right of judicial action: the issue of preferential treatment. Concluding: Judicial Review or Political Review? Abstract: This article addresses the existing problems generated by the parliamentary decision in the granting or denial of requests made by the Supreme Court to the Parliament, in order to remove an MP’s parliamentary immunity, so that (s)he can be prosecuted. Such problems are studied both from the perspective of law and of political science. To this end, this paper analyzes and updates the research done to date about the parliamentary praxis on this issue, highlighting the doctrine which emanates from the decisions adopted by the competent parliamentary committees. In order to understand well the interaction between the praxis, politics and law, this paper also examines the most prominent changes and milestones in the evolution of the constitutional case law on the limits of the Parliament’s capacity to grant or to deny the Supreme Court request asking Parliament to remove an MP’s parliamentary immunity so that (s)he can be prosecuted. For this purpose, the paper systematizes the key points of the academic debate concerning the successive decisions of the Constitutional court: the repercussions of this jurisprudence vis-à-vis the constitutional postulates of separation and independence of State powers, the legal criteria that such postulates must inspire and in order to guide the Parliament in its decision to grant or deny the petition, the concretization of the model and the balance needed in cases of collision of two fundamental rights (in this case, articles 23 and 24 of the Spanish Constitution).